Typologia nauczycielskiej refleksji dotyczącej pracy z uczniami - Joanna Szymczak (Problemy Wczesnej Edukacji)
The article constitutes an attempt to present a typology of reflection concerning working with students, which was constructed due to the work with an empirical data. The main aim of this paper was to provide answers to questions of in what way and with reference to what the early education teachers taking part in the research made a reflection concerning working with students. There was implied a specific research way, whose construction and participation in provided an opportunity to recreate this typology. Theoretical and methodological solutions (and their value for the project) used in the research process were highlighted. In addition, the article comprises the role which may be played in the educational practice – especially with reference to the work with teachers (-to-be)– by the typology documented in the data.